Natural disasters support authoritarian populism: Evidence from the Brazilian shrimp vote - Diogo Baerlocher; Renata de Melo Caldas; Francisco Calcavanti; Rodrigo Schneider (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2022)
We investigate the effects of extreme weather events on voicing political opposition against authoritarian regimes. We use the Brazilian general elections of 1982 as a case study. At the time, Brazil was under a military dictatorship that promoted local and gubernatorial elections to validate its authoritarian power. This context provides a positive measure of protest coined shrimp vote. Moreover, during the elections, the country's northeastern region was facing a long-lasting drought that started in 1979. Using data from meteorological ground stations to compute a measure of drought severity that takes rainfall and evaporation into account, we estimate the effects of the drought on the voting behavior of individuals in this region. Our findings suggest a negative causal effect of adverse weather shocks on the share of protest votes. Specifically, a one-standard-deviation from the historical average water deficit reduces the share of shrimp vote by 2.5%. We also test for heterogeneity among factors such as relief transfers, clientelism, social vulnerability, and economic vulnerability. We only find heterogeneous effects for economic vulnerability. Namely, municipalities whose economy depended less on weather-resistant crops featured stronger declines in protest in response to drought severity.
Keywords: D72; H76; Q54; 330; Natural Disasters; Drought; Democracy; Authoritarianism; Economic Development